2009
DOI: 10.1295/polymj.pj2009110
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Performance of Polyamide 6/Halloysite Nanotubes Nanocomposites

Abstract: Halloysite nanotubes (HNTs) are chemically modified via silylation with 3-(trimethoxysilyl)propyl methacrylate. The modified HNTs (m-HNTs) are characterized by diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy, solid state 13 C NMR spectroscopy, thermogravimetric analysis (TGA) and extraction experiment. It is showed that the silane has been effectively grafted onto HNTs surface and renders the hydrophobicity to m-HNTs. The nanocomposites consisting of polyamide 6 (PA6) and m-HNTs show signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 28 publications
(25 reference statements)
3
49
0
2
Order By: Relevance
“…Nanosilica and talc can also be grafted by PMMA for the purposed of toughening PVC [5,6]. Halloysite nanotubes (HNTs) are a type of natural aluminoslicate nanotube and can be used as nanofiller for polymers, such as polypropylene [7,8], epoxy resin [9][10][11], polyethylene [12], polyamide [13,14] and rubber [15][16][17]. Due to their unique structure, HNTs show promising reinforcing effect for polymers.…”
mentioning
confidence: 99%
“…Nanosilica and talc can also be grafted by PMMA for the purposed of toughening PVC [5,6]. Halloysite nanotubes (HNTs) are a type of natural aluminoslicate nanotube and can be used as nanofiller for polymers, such as polypropylene [7,8], epoxy resin [9][10][11], polyethylene [12], polyamide [13,14] and rubber [15][16][17]. Due to their unique structure, HNTs show promising reinforcing effect for polymers.…”
mentioning
confidence: 99%
“…The glass transition temperature is presented in Figure 7. It can be seen that the T g improvement due to the restriction of the segmental motion of the polymers chain located near the halloysite nanoclay surface [43]. The maximum T g increased from 71.9˚C to 75.9˚C in case of 0.7 wt% reinforcement.…”
Section: Resultsmentioning
confidence: 91%
“…By changing the performance of hydrophobicity, to improved the dispersibility and interfacial interaction between HNTs and polymers. Guo et al (2009) [20] synthesized a high strength nanocomposite (polyamide 6/halloysite) by combined with 3-(trimethoxy silyl) propyl methacrylate. The results showed that the nanocomposites significantly improve mechanical and thermal properties.…”
Section: Coupling Agent Modificationmentioning
confidence: 99%